Gender Differences And Psychological Impacts In Higher Education During Covid-19 Pandemic - Iswadi, Iswadi; Apriyanto, Apriyanto (Universitas Indraprasta PGRI, 2021)
E-learning during covid-19 pandemic gives positive and negative effects on students’ psychology. One of the effects of E-Learning is students whose negative and positive perception towards the process of E-Learning. The objectives of the study are to know (1) The difference perception between male and female EFL post-graduate students of the use of online learning platforms? (2). Impacts psychologically of E-learning during Covid-19 to female and male EFL students in higher education. The method of the study is mixed research with the explanatory sequential design. The participants were 31 EFL postgraduate students in PGRI Indraprasta University. The data collection technique of the study was questionnaires with a Likert scale and an open interview. The data analysis technique of the study is an independent sample t-test with SPSS 22.0 version and collection, reduction, display, and conclusion. The results of the study are: (1) There is no significant difference perception between male and female EFL postgraduate students of the use of online learning platform because the significance value (0.695) which is bigger than 0.05. (2) E-learning during the Covid-19 pandemic did not give anxiety, fear, fatigue, and saturation to female and male EFL students in higher education. Implication of this research is University must develop LMS (Learning Management System) for teaching EFL students